ASPECTS REGARDING ENVIRONMENTAL ASSESSEMENT AND MODELING (PANGEEA, 2025)
The environmental modelling have attracted a lot of attention in the past years. Their capacity to learn non-linear relationships between an input and an output space has a lot of applications: modeling and controlling dynamic processes and systems, signal processing, pattern recognition, forecast, climate prediction etc. This paper will approach a specific area from the large field of applications:identifyingandmodeling of some dynamic processes like pollution and energy management. We briefly introduce a series of the oretical considerations on process modeling and then we present several results obtained by the authors in modeling, and environmental mapping of the pollution process in Zlatna region.
Keywords: Modelling; ANN; environmental mapping; pollution; Spatial system; environmental reconstruction